Bat Nipah Virus, Thailand - Wacharapluesadee, Supaporn (Centers for Disease Control and Prevention, 2005)
Surveillance for Nipah virus (NV) was conducted in Thailand's bat population. Immunoglobulin G antibodies to NV were detected with enzyme immunoassay in 82 of 1,304 bats. NV RNA was found in bat saliva and urine. These data suggest the persistence of NV infection in Thai bats.